Relations between assumptions of human nature and work and leadership style preferences - Mitrić-Aćimović, Dragana; Vujić, Dobrila; Dostanić, Jelena (Primenjena psihologija, 2012)
This research explores the relationship between the assumptions of human nature and work and leadership style preferences. The survey was conducted in a convenient sample of 288 employees (217 employees and 71 managers), in several companies of various sizes and ownership structures. The assumptions of human nature and work, as defined in the Steers and Porter’s model (Steers & Porter, 1987), were measured using an adjusted scale, based on this model. The leadership style was two-dimensional: Autocratic/ Democratic and Orientation toward People/Orientation to Tasks. These dimensions were measured using the STIL-RUK, a questionnaire for managers slightly modified for the purposes of this research. The results of multiple regression analyses showed that the assumption of man as a social being and man as a creative being predicted preferences for democratic leadership and orientation toward people, whereas the assumption of man as a rational–economic being was not a significant predictor of leadership style preference. The results showed that the democratic leadership style was more preferable among women than men, while task-oriented leadership was more preferable by managers than employees. Age and years of service were not correlated with the preferred style of leadership. These findings suggest that our respondents who have assumptions of people as rational-economic beings do not prefer appropriate practical approach to management, which was expected. The results are consistent with the findings of previous studies, because two of three types of observed assumptions of human nature acted only as correlates of leadership style.